1991
DOI: 10.7589/0090-3558-27.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Helminth Parasitism in Bobwhites From Northern Florida

Abstract: Examination of 700 northern bobwhites (Colinus virginianus), 50 each February from 1971 through 1984, from Tall Timbers Research Station, Leon County, Florida, disclosed 15 species of helminth parasites. Nine species (Raillietina cesticillus, R. colinia, Aproctella stoddardi, Cheilospirura spinosa, Cyrnea colini, Dispharynx nasuta, Heterakis isolonche, Tetrameres pattersoni, and Trichostrongylus tenuis) generally were found on an annual basis and were considered characteristic components of the helminth fauna.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Conversely, in red grouse, T. tenuis causes disease in individuals and can regulate host populations (Shipley 1911;Wilson and Leslie 1911;Hudson and Dobson 1991;Hudson et al 1992aHudson et al , b, 1998. Trichostrongylus cramae intensity in APCs (x -=1,019.3; Range=3-1,906; N=3) appears more similar to that seen for T. tenuis in red grouse in northern England and Scotland (Hudson 1986, Shaw and Moss 1989, Hudson et al 1992a), than to T. cramae in northern bobwhites in the southeastern United States (Forrester et al 1984, Moore et al 1986, Davidson et al 1991, Purvis et al 1998. Because cecal length of Tympanuchus spp.…”
Section: Macroparasitesmentioning
confidence: 84%
“…Conversely, in red grouse, T. tenuis causes disease in individuals and can regulate host populations (Shipley 1911;Wilson and Leslie 1911;Hudson and Dobson 1991;Hudson et al 1992aHudson et al , b, 1998. Trichostrongylus cramae intensity in APCs (x -=1,019.3; Range=3-1,906; N=3) appears more similar to that seen for T. tenuis in red grouse in northern England and Scotland (Hudson 1986, Shaw and Moss 1989, Hudson et al 1992a), than to T. cramae in northern bobwhites in the southeastern United States (Forrester et al 1984, Moore et al 1986, Davidson et al 1991, Purvis et al 1998. Because cecal length of Tympanuchus spp.…”
Section: Macroparasitesmentioning
confidence: 84%
“…Although very little is known about the pathogenicity of parasites in wild birds, we also found no sign of any pathological condition, nor any significant correlation between levels of helminth infection and Greywing body mass. Davidson et al (1991) reported that helminth burdens of Aproctella stoddardi and Dispharynx nasuta did not vary with Bobwhite population density because they occurred in a broad range of definitive hosts. This possibly also accounts for the lack of significant correlation between helminth burdens and Greywing population density in this study.…”
Section: Discussion In These Greywing As In Helmeted Guineafowlmentioning
confidence: 97%
“…When Cram ( b ) initially described T. pattersoni from wild bobwhites collected in North Carolina, she described heavy infections (up to 21 F and 7 M in 1 host) that covered nearly the entire wall of the proventriculus. Davidson et al () found this nematode in 21.7% of bobwhites sampled at the Tall Timbers Research Station in Florida, USA, and noted inflammation and localized tissue damage associated with T. pattersoni infections. The heavy infections described by Cram () were not encountered in 3 recent surveys in Texas (Villarreal , Bruno , Olsen ).…”
Section: Recent Research On Helminth Parasitism In Bobwhitesmentioning
confidence: 99%